INTERRELATION OF ISLAM AND TRADITIONAL JAVA - Tri Wahyudi Ramdhan (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2020)
The interrelation between religion and culture is very closely related to the traditions of human life so that religion often gives birth to culture or civilization for the enjoyment of human life on the surface of the earth. In the view of some sociologists, it is said that Islam is called the religion of civilization. In the case of the interrelation between religion and culture for the Javanese as the majority ethnic group in the archipelago, it is an interesting thing to study. Islam entered Java in a peaceful way, starting with the common people until gradually entering the palace level. The Javanese responded well to the entry of Islam to Java. Because Islam easily socializes with Javanese people. Javanese people are fascinated by Islamic teachings that introduce the unity of Allah. Islam is mixed with Javanese culture because Islam is intended to facilitate the spread of its religion. However, until now, Javanese culture is still attached to Islamic teachings, which are still mostly adhered to by Javanese people. Thus the author tries to discuss how the true beliefs that develop from the interrelation of religion (Islam) and Javanese culture, the response of Javanese culture to Islam and the response of Islam to Javanese culture.